The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.rser.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting techniques applied to microalgae: A review

Abstract: Research studies on microalgae have increased in the last decades due to the wide range of applications associated to these photosynthetic microorganisms. Microalgae are an important source of oils and other biomolecules that can be used in the production of biofuels and high-valued products. However, the use of microalgae in these green processes is still not economically viable. One of the main costs associated to microalgal production is related to the harvesting process, as it usually accounts for about 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
355
0
37

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 777 publications
(394 citation statements)
references
References 69 publications
2
355
0
37
Order By: Relevance
“…Although sedimentation and flotation are commonly used as algae harvesting methods on a large scale, valuable nutrients are removed with the algal biomass in these processes, which lowers the value of the recycled media. The residual coagulants in the recycled media are also problematic for algae growth [18]. Membrane separation could successfully avoid the above disadvantages [19] and provides purified media which is the most suitable for reuse for the subsequent cultivation of microalgae [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although sedimentation and flotation are commonly used as algae harvesting methods on a large scale, valuable nutrients are removed with the algal biomass in these processes, which lowers the value of the recycled media. The residual coagulants in the recycled media are also problematic for algae growth [18]. Membrane separation could successfully avoid the above disadvantages [19] and provides purified media which is the most suitable for reuse for the subsequent cultivation of microalgae [20].…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae can be used as feedstock for the production of biofuels such as biodiesel, biomethane, bioethanol, biohydrogen and biobutanol [1,2] also can be used in the synthesis of different high-valued compounds, such as supplements for animal and aquaculture feed, cosmetics and pharmaceuticals [2]. Regarding the environment, microalgae can play an important role in treatment of wastewater also carbon dioxide sequestration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of microalgae in these green processes is still not economically viable. One of the main costs associated to microalgal production is the harvesting one, as it usually accounts for about 20-30 % of total cost [1]. Microalgae can be harvested by a number of methods such as sedimentation, flocculation, flotation, centrifugation and filtration or a combination of any of these [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barros et al showed in their investigation that biomass recovery efficiency above 90% of Dunaliella tertiolecta microalgae was reached when the pH was brought to values of 10.5 by adding of NaOH. It can be due to neutralization of the charges present at the microalgae surface with consequent formation of large aggregates and subsequent sedimentation [3]. Furthermore, this low cost harvesting method allows reuse the culture medium by pH neutralization.…”
mentioning
confidence: 99%